2014
DOI: 10.1108/s0742-730120140000032005
|View full text |Cite
|
Sign up to set email alerts
|

The role of reputation in the organizational sciences: A multilevel review, construct assessment, and research directions

Abstract: Scholarship on reputation in and of organizations has been going on for decades, and it always has separated along level of analysis issues, whereby the separate literatures on individual, group/team/unit, and organization reputation fail to acknowledge each other. This sends the implicit message that reputation is a fundamentally different phenomenon at the three different levels of analysis. We tested the validity of this implicit assumption by conducting a multilevel review of the reputation literature, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 145 publications
2
52
0
4
Order By: Relevance
“…In regards to occupational status, it has been argued that those with a favourable reputation are viewed as more competent and often gain higher status (Tsui, 1984). One study found that reputation mediated the influence of individual differences on career success (Zinko, Ferris, Humphrey, Meyer, & Aime, 2012), and it has been argued that personality identity is an antecedent of reputation and that career success is a consequence of reputation (Ferris et al, 2014;Hogan & Shelton, 1998). We believe that targets having a higher reputation for achievement orientation (i.e., persons that are viewed as ambitious, efficient, competent, and successful) are more likely to gain a prestigious position with higher status, as groups use their perceptions of individuals' desired attributes to award higher and lower status (Anderson & Cowan, 2014).…”
Section: Personality Identity Personality Reputation and Occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to occupational status, it has been argued that those with a favourable reputation are viewed as more competent and often gain higher status (Tsui, 1984). One study found that reputation mediated the influence of individual differences on career success (Zinko, Ferris, Humphrey, Meyer, & Aime, 2012), and it has been argued that personality identity is an antecedent of reputation and that career success is a consequence of reputation (Ferris et al, 2014;Hogan & Shelton, 1998). We believe that targets having a higher reputation for achievement orientation (i.e., persons that are viewed as ambitious, efficient, competent, and successful) are more likely to gain a prestigious position with higher status, as groups use their perceptions of individuals' desired attributes to award higher and lower status (Anderson & Cowan, 2014).…”
Section: Personality Identity Personality Reputation and Occupationmentioning
confidence: 99%
“…In the present study, we utilize political skill (Ferris et al, 2014) as a moderator of the personality identityreputation relationship. Politically skilled individuals are adept at understanding and interpreting others and social situations, and they portray themselves and their desires in ways that influence coworkers (Ferris et al, 2005).…”
Section: Socioanalytic Theory Personality and Political Skillmentioning
confidence: 99%
“…De acuerdo con Ferris et al (2014) no existe una teoría de la reputación. Sugieren que su análisis se plantea desde diversos postulados como: 1. teoría de señales (signalling theory); 2. teoría de la comparación social (social comparison theory); y 3. teoría de la influencia social y gestión de impresiones (social influence and impression management theory).…”
Section: Principales áReas Enfoques Y Autores Que Han Estudiado La Runclassified
“…Ellos sostienen que está íntimamente ligado con la naturaleza de la reputación porque las acciones del individuo se sujetan a un período y acontecen en uno o varios momentos de su historia personal (Zinko, 2012). Por lo tanto, la reputación no es estática sino dinámica porque aparece, crece y cambia con el tiempo (Ferris, 2014).…”
Section: Imagenunclassified
“…Reputation is a mechanism that reduces complexity in decision making (Ferris et al 2014;Ching et al 1992), so evaluators will direct their limited attention and cognitive resources to ideas submitted by employees who signal better innovation capabilities. Specifically, inventors' experience in patenting, scientific publishing, and idea generation is an objective indicator of innovation capabilities (Subramanian et al 2013).…”
Section: Hypotheses About the Decision-making Of Committees And Crowdsmentioning
confidence: 99%